Using Artificial Intelligence in Writing an Academic Essay: A Literature Review - Sari, Nella Ardhita Pramita (PROJECT (Professional Journal of English Education), 2025)
Writing an academic essay might be challenging for English as a Foreign Language (EFL) students. As a response, the researcher is interested in investigating EFL university students' perspectives on using Artificial Intelligence technology to help them improve their academic essays. To achieve the research goal, the researcher first did a literature review analysis on seventeen articles published in national and international journals. After the review analysis, the researcher interviewed five participants who are now or have taken academic essay writing classes in batch 2021 or 2022 to discuss the results of the literature review analysis. This interview served as an insight into the experiences and perceptions of EFL students regarding the benefits and limitations of AI in academic writing. The data was qualitatively examined and presented as themes. The study results showed that the participants generally had positive perspectives when using AI technology. The study was expected to provide an overview of the benefits experienced by students and potential limitations of AI in essay writing, thus providing valuable insights for educators who wish to integrate AI in academic writing classes. The study concluded with recommendations for further research on the role of AI in EFL academic writing support.